2016
DOI: 10.4329/wjr.v8.i5.501
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy of parotid masses: Review of current techniques

Abstract: Definitive diagnosis of parotid gland masses is required optimal management planning and for prognosis. There is controversy over whether fine needle aspiration cytology (FNAC) or ultrasound guided core biopsy (USCB) should be the standard for obtaining a biopsy. The aim of this review is to assess the current evidence available to assess the benefits of each technique and also to assess the use of intra-operative frozen section (IOFS). Literature searches were performed using pubmed and google scholar. The li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 29 publications
1
31
1
1
Order By: Relevance
“…FNA is commonly reported to have fewer complications when compared to core biopsy and with less potential for tumor seeding . Nonetheless, some recent studies question this assumption and defend the use of core biopsy as safe and with potentially superior diagnostic yield . Notwithstanding, FNA is certainly a less costly option which can be performed on a one‐stop clinic setting and most studies find it an excellent pre‐surgical triage tool, distinguishing accurately neoplastic from non‐neoplastic lesions …”
Section: Discussionmentioning
confidence: 99%
“…FNA is commonly reported to have fewer complications when compared to core biopsy and with less potential for tumor seeding . Nonetheless, some recent studies question this assumption and defend the use of core biopsy as safe and with potentially superior diagnostic yield . Notwithstanding, FNA is certainly a less costly option which can be performed on a one‐stop clinic setting and most studies find it an excellent pre‐surgical triage tool, distinguishing accurately neoplastic from non‐neoplastic lesions …”
Section: Discussionmentioning
confidence: 99%
“…FNAC can be subject to sampling bias, particularly if the tumor is in the deep lobe of the parotid (Thoeny, ). Not least, some authors have reported cases of tumor capsule seeding following FNAC procedures (Freling, Crippa, & Maroldi, ; Haldar, Sinnott, Tekeli, Turner, & Howlett, ; Sood, McGurk, & Vaz, ). Other diagnostic imaging techniques such as magnetic resonance imaging (MRI), computed tomography (CT), and ultrasonography (US) have been found highly beneficial in the diagnosis of SGC tumor location, extent, and the presence of perineural invasion (Haldar et al, ; Rudack, Jörg, Kloska, Stoll, & Thiede, ).…”
Section: Introductionmentioning
confidence: 99%
“…Not least, some authors have reported cases of tumor capsule seeding following FNAC procedures (Freling, Crippa, & Maroldi, ; Haldar, Sinnott, Tekeli, Turner, & Howlett, ; Sood, McGurk, & Vaz, ). Other diagnostic imaging techniques such as magnetic resonance imaging (MRI), computed tomography (CT), and ultrasonography (US) have been found highly beneficial in the diagnosis of SGC tumor location, extent, and the presence of perineural invasion (Haldar et al, ; Rudack, Jörg, Kloska, Stoll, & Thiede, ). Although revision of the current preoperative diagnostic approaches is deemed necessary, as neither CT, US nor MRI was found to be superior in the diagnostic work‐up of SGCs (Rudack et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The present case showed clear microscopic features of PAC, in addition there is no conclusive evidence that (MASC) should be treated differently than any other low-grade malignant salivary gland tumors, though when used in conjunction with a cytology and Image guidance. In the present case US was used to guide fine needle aspiration cytology (FNAC) to overcome sampling error [15,16] . CT with contrast is the most commonly used investigation in diagnosis of salivary tumors.…”
Section: Discussionmentioning
confidence: 99%